Simultaneous Determination of 14 Compounds in Gegen Qinlian Tablet by HPLC - Shi, Zhihong; Li, Zhimin; Li, Qi; Zhang, Shulan; Zhang*, Hongyi (Asian Journal of Chemistry, 2014)
A high performance liquid chromatographic method was established for the simultaneous determination of puerarin, daidzin, scutellarin, liquiritin, baicalin, jatrorrhizine, coptisine, daidzein, palmatine, berberine, wogonoside, glycyrrhizic acid, baicalein and wogonin in Gegen Qinlian Tablet. All the 14 compounds were separated on a Dikma C18 column (150 × 4.6 mm i.d., 5 μm) by gradient elution. The mobile phase consisted of ammonium formate buffer solution (20 mmol L-1, pH 3.2, adjusted by formic acid) (A) and acetonitrile (B) at a flow rate of 1 mL min-1. The ultraviolet detection was accomplished at 254 and 275 nm. The RSD values for intraday precision (n = 6) and interday precision (n = 5) were less than 2.04 and 2.59 %, respectively. The recoveries were in the range of 91.6-101.3 %. Using ethanol-water (60:40, v/v) as extractant, this method was successfully applied to the quality evaluation of Gegen Qinlian tablets.